FORMULATION OF LIP TINT FROM EXTRACTS OF KEPOK BANANA FLOWER (Musa paradisiaca Linn.) AND DRAGONFRUIT (Hylocereus polyrhizus) AS NATURAL COLOURS - Sudirman, Agriawan; Asri SR, Muhammad; Dahlia (STIKES Nani Hasanuddin Makassar, 2024)
Lip tint is a cosmetic preparation used to color lips which has liquid texture with a more natural color so that it is easily absorbed and produces a natural color like the lips’ original color. This research aimed to determine whether kepok banana flower peel extract (Musa paradisiaca Linn.) and dragon fruit (Hylocereus polyrhizus) can be formulated in the from of lip tint preparations as natural dyes and to test the antioxidant activity of lip tint preparations. The research method was experimental research by making lip tint formulations with concentrations of FI (2%), FII (6%), and FIII (10%) from banana peel and dragon fruit extracts, evaluating the preparations using physicochemical methods and testing antioxidant activity using the method DPPH using a UV-Vis spectrophotometer. The results showed that the total anthocyanin content in the peel of the kepok banana flower was 0,374 mg/L and in dragon fruit it was 8,232 mg/L. Lip tint preparation formulas with concentrations of 2%, 6% and 10% are physically and chemically stable and the antioxidant activity test in Formula I (2%) obtained an IC50 value of 3,52 µg/mL, Formula II (6%) obtained an IC50 value of 3,91 µg/mL, Formula III (10%) obtained an IC50 value of 1,62 µg/mL and in the positive control comparison (Lip Tint Implora®) an IC50 value of 1,98 µg/mL was obtained. The formula with a concentration of 10% has an IC50 value of 1,62 µg/mL in the very strong category.